Health professionals interface with cultural conflict in the delivery of type 2 diabetes care. Issue 2 (1st February 2023) - Patel, Tasneem; Umeh, Kanayo; Poole, Helen; Vaja, Ishfaq; Ramtoola, Shenaz; Newson, Lisa
Abstract: Objective: This study explored the knowledge and experiences of health professionals (HPs) caring for South Asian patients with type 2 diabetes (T2D). Design: Fourteen HPs, who supported patients with T2D, were interviewed. The recruitment strategy employed purposeful and theoretical sampling methods to recruit HPs who worked across primary and secondary care settings. Main Outcome Measures: Grounded Theory (GT) methodology and analysis generated a theoretical framework that explored HP's perceptions and experiences of providing diabetes care for South Asian patients. Results: A GT, presenting a core category of Cultural Conflict in T2D care, explores the influences of HP's interactions and delivery of care for South Asian patients. This analysis is informed by four categories: (1) Patient Comparisons: South Asian vs White; (2) Recognising the Heterogeneous Nature of South Asian Patients; (3) Language and Communication; (4) HPs' Training and Experience. Conclusions: The findings consider how the role of social comparison, social norms, and diminished responsibility in patient self-management behaviours influence HPs' perceptions, implicit and explicit bias towards the delivery of care for South Asian patients. There was a clear call for further support and training to help HPs recognise the cultural-ethnic needs of their patients.